Penguatan Pemahaman Moderasi Beragama melalui Literasi Media pada Kementerian Agama Luwu Utara: Upaya Penguatan Pemahaman Moderasi Beragama pada Kementerian Agama Luwu Utara - Rahman, Saifur; Hasyim, Baso; Alfauzie, Risaldi; Musfira, Andi (Islamic Management and Empowerment Journal, 2024)
This article discusses community service efforts carried out in the North Luwu area with a focus on strengthening the understanding of religious moderation through media literacy. This program is aimed at employees of the North Luwu Ministry of Religion with the aim of strengthening national commitment, reducing violence, increasing tolerance, and promoting respect for local wisdom in a religious context. The methods used in this service involve training, workshops and participatory approaches to improve participants’ understanding and media literacy skills.